Parents' perceptions of children's emotional well‐being during spring 2020 COVID‐19 restrictions: A qualitative study with parents of young children in England. (2nd August 2022) - Chambers, Stephanie; Clarke, Joanne; Kipping, Ruth; Langford, Rebecca; Brophy, Rachel; Hannam, Kim; Taylor, Hilary; Willis, Kate; Simpson, Sharon A.
Abstract: Background: During COVID‐19 restrictions in England in spring 2020, early years settings for young children were closed to all but a small percentage of families, social contact was limited and play areas in parks were closed. Concerns were raised about the impact of these restrictions on young children's emotional well‐being. The aim of this study was to explore parents' perceptions of young children's emotional well‐being during these COVID‐19 restrictions. Methods: We interviewed 20 parents of children 3–4 years due to begin school in England in September 2020. Interviews were conducted via telephone ( n = 18) and video call ( n = 2), audio‐recorded and transcribed verbatim. Interviews focused on childcare arrangements, children's behaviour and transition to school. A sample of transcripts were coded line by line to create a coding framework, which was subsequently applied to the remaining transcripts. Coded data were then analysed using a nurture lens to develop themes and further understanding. Results: Participants were predominantly mothers ( n = 16), White British ( n = 10) and educated to degree level ( n = 13), with half the sample living in the highest deprivation quintile in England ( n = 10). Five were single parents. Three themes developed from nurturing principles were identified: creating age‐appropriate explanations, understanding children's behaviour and concerns about school transition. Parents reported that their children's emotional well‐being was impacted and described attempts to support their young children while looking ahead to their transition to primary school. Conclusions: This study is one of the first to examine in‐depth perceptions of COVID‐19 restrictions on young children's emotional well‐being. The longer term impacts are not yet understood. Although young children may be unable to understand in detail what the virus is, they undoubtedly experience the disruption it brings to their lives. The well‐being of families and children needs to be nurtured as they recover from the effects of the pandemic to allow them to thrive.